Peningkatan Partisipasi Masyarakat dalam Perencanaan Pembangunan di Kabupaten Pasuruan dengan Pendekatan Human Centered Design - Devi Citasari; A’an Warul Ulum (EduInovasi: Journal of Basic Educational Studies, 2025)
Development planning is a strategic process involving various stakeholders in formulating steps to improve community welfare. One crucial element in this process is community participation, which not only reflects democratic rights but also plays a vital role in the success of development programs. This study highlights the low level of community participation in the Development Planning Forum (Musrenbang) in Pasuruan Regency, East Java. The low participation is influenced by several factors, including low educational attainment, work priorities, and a lack of understanding of the importance of involvement in development. Using the Human Centered Design (HCD) approach, this study proposes the application of five HCD stages—Empathize, Define, Ideate, Prototype, and Test—as a model to enhance and sustain community participation in the local development planning process.